2015
DOI: 10.1161/jaha.115.002268
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends and Hospital Variation in Mineralocorticoid Receptor Antagonist Use in Veterans Discharged With Heart Failure

Abstract: BackgroundDespite concerns about mineralocorticoid receptor antagonist therapies (MRAs) underuse and misuse in patients with heart failure, temporal and institutional variations of MRA prescription have not been reported.Methods and ResultsWe studied a national sample of veterans hospitalized for heart failure between 2003 and 2009 and left ventricular ejection fraction <40%. We identified ideal and non‐ideal candidates for MRA therapy based on American College of Cardiology/American Heart Association guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…In addition, we do not have information on the survey respondents' individual MRA‐prescribing behaviors, which would be useful to correlate with their knowledge and awareness of MRAs. We know that our VA medical center has MRA‐prescribing rates (unpublished data) similar to national VA MRA prescribing rates; therefore, it may reasonably represent other VA medical centers. Finally, some participants may have been minimally involved in the care of patients with HF; however, all participants had clinical roles and would be expected to have basic knowledge of HF.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, we do not have information on the survey respondents' individual MRA‐prescribing behaviors, which would be useful to correlate with their knowledge and awareness of MRAs. We know that our VA medical center has MRA‐prescribing rates (unpublished data) similar to national VA MRA prescribing rates; therefore, it may reasonably represent other VA medical centers. Finally, some participants may have been minimally involved in the care of patients with HF; however, all participants had clinical roles and would be expected to have basic knowledge of HF.…”
Section: Discussionmentioning
confidence: 92%
“…12 Of the survey participants, 42 elected to participate in focus groups (ie, 84% recruitment rate) ( Table 1). We convened 6 focus groups, stratified by stakeholder category so as to develop a comfortable group atmosphere and encourage discussion of shared experiences: (1) cardiology nurse practitioners and cardiologists, (2) cardiology fellows in training, (3) hospitalists, (4) clinical pharmacists, (5) internal medicine residents, and Community clinic-rural 3 (6) Total years in practice (including residency), median (IQR)* 9 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) Years in practice at Phoenix VA (including residency),* median (IQR) No response 2 (4) (6) primary care physicians and nurse practitioners. We developed a semistructured focus group guide based on the extant literature regarding barriers to MRA prescription and a preliminary analysis of the aforementioned survey data.…”
Section: Focus Groupsmentioning
confidence: 99%
“…Despite these remarkable improvements in morbidity and mortality, and class IA guideline recommendations, MRAs are still largely underused in routine clinical practice . This may be (at least partly) explained by an undue concern about inducing hyperkalaemia or worsening renal function, and the need for close monitoring of potassium and renal function, but also by a lack of education/promotion about these drugs and their indications …”
Section: Introductionmentioning
confidence: 99%
“… 10 Recently, a national large cohort study revealed that aldosterone antagonists prescription decreased over time in patients with HF. 11 Factors contributing to the discrepancy between current practice and evidence-based guidelines are unclear. The assessment of physicians and pharmacists’ knowledge of guidelines is important to narrow the treatment gap for use of aldosterone antagonists.…”
Section: Introductionmentioning
confidence: 99%